Immune-Related Biomarkers Improve Performance of Risk Prediction Models for Survival in Patients With Hepatocellular Carcinoma - Wan, Haifeng; Lu, Shan; Xu, Lin; Yuan, Kefei; Xiao, Yang; Xie, Kunlin; Wu, Hong (Frontiers in Oncology, 2022)
Object: Prediction of hepatocellular carcinoma (HCC) prognosis faced great challenge due to tumor heterogeneity. The purpose of this study was to explore the correlation between immune infiltrate and prognosis. Moreover, we aimed to establish a risk prediction model for survival in HCC patients based on clinicopathological and immune indicators. Methods: In this study, 316 patients with hepatocellular carcinoma who underwent radical resection in West China Hospital from 2009 to 2014 were included. Clinicopathological data and pathological specimens were collected. H&E staining and immunohistochemical staining were performed on the pathological tissue sections. Evaluation of tumor-infiltrating lymphocytes (TILs) density was based on H&E slices, and assessment of expressions of CD8, CD68, LAG-3, TIM-3, PD-1, PD-L1, OX40, CD66b, and RYPETASE was performed on the immunohistochemical slices. A risk prediction model for survival in HCC patients was established by integrating immune-related biomarkers and clinicopathological indicators. Results: BCLC C stage, micro-vascular invasion status, the density of TILs, expressing levels of CD66b, OX40, PD-L1 in the immune cell, CD68, and CD8 were predictors of patients’ overall survival. BCLC stage, density of TILs, expressions of OX40, CD68, and CD8 were associated with disease-free survival. The expressions of CD66b, CD68, OX40, and CD8 had a cumulative effect on prognosis. The AUC of the prediction model for overall survival based on clinicopathological features was improved from 0.62 to 0.74 by adding to CD8, OX40, CD68, CD66b, and TILs, whereas it was improved from 0.59 to 0.73 for the disease-free survival prediction model. Conclusion: Our results, if confirmed, indicated that immune-related biomarkers should be taken into account or stratified in survival analysis for hepatocellular carcinoma.